GENERATION OF SOLITARY WAVE PACKETS IN REAL WAVEGUIDES - Khamidullin Y.N. (My University, 1988)
The paper presents some results of drillhole logging studies in coal seams that function as seismic waveguides. The use of pulsed elastic-wave generators makes it difficult to identify nonlinear interaction of seismic waves, therefore the study focuses primarily on the temporal and spatial evolution of the general wave pattern. These observations are of interest in elucidating the mechanism of elastic energy transport in the earth's interior under impact excitation, in which self-focusing and self-modulation of seismic waves may occur, giving rise to solitary wave packets with soliton-like properties. The study used a ShSA-2 ten-channel downhole apparatus operating in the frequency range of 60 to 500 Hz and with maximum sensitivity in the 60 to 200 Hz interval. The seismic waves were excited by 200-gram explosive charges and detonators, or with a thumper. Study results are discussed.